English communication skills of IIUM English graduates : a study - Zarrin, Naeylah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The purpose of this study is to determine the English communication skills of IIUM English graduates and aims to answer three substantial research questions, such as the expectations of the employers of the IIUM English graduates, graduates meeting the expectations of the employers and areas of improvement needed for the IIUM English graduates. The study draws upon the case study of 100 employers who either employ or have had experiences of employing IIUM English graduates. The study was conducted through triangulation of data collected from questionnaires and in-depth interviews with employers. SPSS was used to analyze the results before they were translated into research data. The demographics of the employers who responded were 71.8% male managers and 28.2% female managers. 81% of the companies that responded were private companies owned locally and multinational companies, while the other 19% were government-owned and NGOs. The study reveals that IIUM English graduates have good language proficiency as well as good public speaking skills; however, the employers felt that interpersonal skills of the graduates need improvement.